Deep Brain Stimulation for Refractory Obsessive-Compulsive Disorder: Towards an Individualized Approach - Senova, Suhan; Clair, Anne-Hélène; Palfi, Stéphane; Yelnik, Jérôme; Domenech, Philippe; Mallet, Luc (Frontiers in Psychiatry, 2019)
Obsessive-Compulsive Disorder (OCD) is a neuropsychiatric disorder comprises repetitive intrusive thoughts and behaviours leading to significant handicap. 20% of patients are refractory to medication and cognitive behavioural therapy. Refractory OCD is associated with suicidal behaviour and significant degradation of social and professional functioning, with high health costs. Deep Brain Stimulation (DBS) has been proposed as a reversible and controllable method to treat refractory patients with meta-analyses showing 60% response rate following DBS (>35% of decrease on the Y-BOCS severity scale), whatever the target: anterior limb of the internal capsule (ALIC), ventral capsule/ventral striatum (VC/VS), nucleus accumbens (NAcc), anteromedial subthalamic nucleus (amSTN) or inferior thalamic peduncle (ITP). But how do we choose the “best” target? Functional neuroimaging studies have shown that successful ALIC-DBS requires modulation of the fibre tract within the ventral ALIC via the ventral striatum, bordering the bed nucleus of the stria terminalis (BNST) and connecting medial prefrontal cortex (mPFC) with the thalamus. VC/VS effective sites of stimulation were found within the VC and primarily connected to medial orbitofrontal cortex (OFC) dorsomedial thalamus, amygdala and the habenula. NAcc-DBS has been found to reduce OCD symptoms by decreasing excessive fronto-striatal connectivity between NAcc and the lateral prefrontal cortex (lPFC) and mPFC. The amSTN effective stimulation sites are located at the inferior medial border of the STN, primarily connected to lateral OFC, dorsal anterior cingulate (DACC) and dorsolateral prefrontal cortex (DLPFC). Finally, ITP-DBS recruits a bidirectional fibre pathway between the OFC and the thalamus. Thus, these functional connectivity studies show that the various DBS targets lie within the same diseased neural network. They share similar efficacy profiles on OCD symptoms as estimated on the Y-BOCS, the amSTN being the target supported by the strongest evidence in the literature. VC/VS-DBS, amSTN-DBS and ALIC-DBS were respectively also found to improve mood, behavioural adaptability and potentially both. Because OCD is such a heterogeneous disease with many different symptom dimensions, the ultimate aim should be to find the most appropriate DBS target for a given refractory patient. This quest will benefit from further investigation and understanding of the individual functional connectivity of OCD patients.